Ibn Rushd and contemporary Russian orientalism - Ali, Duaa; Madi, Ahmad; Dababseh, Hamed (Research Journal in Advanced Humanities, 2024)
Researchers embarked on the thrilling journey of exploring the authors’ view on the philosophy of Ibn Rushd in Russian, and the triggers behind its preparation, which is the lack of any Russian study on Ibn Rushd among Arabs who searched the philosophy of Ibn Rushd and misses the writing of Russian authors on the philosophy of Ibn Rushd, or even among other Arabs philosophers who were specialized in Russian. The researchers saw Artur Saadi as the most important student of this philosophy, in which he wrote a book in Russian that was translated into Arabic.